PENGARUH BRISK WALKING EXERCISE TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DIWILAYAH KERJA PUSKESMAS KEMBARAN I - Sayogi Priambodo; Maya Safitri; Feti Kumala Dewi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Hypertension is a prevalent health problem that increases the risk of cardiovascular complications. In addition to pharmacological therapy, non-pharmacological interventions such as brisk walking exercise play an important role in helping control blood pressure. This study aimed to analyze the effect of brisk walking exercise on blood pressure reduction among patients with hypertension in the working area of Puskesmas Kembaran 1, Banyumas Regency. This research employed a quasi-experimental design with a one-group pretest–posttest approach. A total of 32 respondents were selected using purposive sampling, consisting of hypertensive patients without complications and with stable conditions. The intervention consisted of brisk walking exercise performed for three consecutive days, 15 minutes per session. Blood pressure was measured 30 minutes before and after each intervention using a sphygmomanometer and stethoscope. Data analysis used the paired t-test for systolic pressure and the Wilcoxon test for diastolic pressure. The results showed that most respondents were late elderly (56.3%), female (62.5%), and had a family history of hypertension (65.6%). The mean blood pressure before the intervention was 149.47 mmHg (systolic) and 89.97 mmHg (diastolic). After the intervention, it decreased to 142.09 mmHg and 84.38 mmHg, respectively. Statistical tests indicated a significant reduction in systolic (7.38 mmHg) and diastolic pressure (5.59 mmHg) with p = 0.0001. The study concludes that brisk walking exercise has a significant effect on reducing blood pressure among hypertensive patients. This intervention is recommended as a simple, safe, and affordable strategy for hypertension management in primary health care settings